Mechanism of Extruding Flowing Floor Heave in Mining Gateways Using an Elastic Foundation Beam Model - Pan Chen; Yuan-Xiang Yu; Shuan-Cheng Gu (Advances in Civil Engineering)
Considering the action of high bearing pressures, a mechanical model of a coal wall mining gateway is established based on the elastic theory. The stress-strain distribution of the coal body is also discussed. According to the compression column model, under the action of the peak-bearing pressure, the maximum horizontal tensile strain in the coal wall is located at 0.65 times the height of the roadway. Furthermore, a theoretical formula for the limit equilibrium zone width and the ultimate tensile strain of the coal body was proposed. The results show that the width of the limit equilibrium zone of the coal wall is related to the ultimate tensile strain of the coal body, the maximum bearing pressure, Poisson’s ratio, the elastic modulus, the original rock stress, and the width of the elastic zone. The maximum shearing breakage depth and position of the floor rock under the plastic flow extruded through coal walls are discussed. Finally, taking the 350–450 m section of the transportation lane in the 14501 working face of Bailiang coal mine as an example, the limit equilibrium of the wall width and the floor breakage depth are calculated on the basis of the relevant parameters. Based on the results, bolt support parameters are designed, which enhance the stability of surrounding rock significantly, providing a theoretical reference for the prevention of liquid gateway floor heave.